The decision to migrate and social capital: Evidence from Albania - Cristina Cattaneo (Fondazione Eni Enrico Mattei (FEEM), 2009)
The objective of this paper is to determine whether the participation in social organizations, which are commonly defined as a form of social capital, represents a complement or a substitute with respect to emigration. The nature of the relationship depends on the motivations behind the two choices, which induce the households to join a group and to invest in migration. To address this research question a bivariate probit model is employed, in that the decision to migrate and to join a social organization are estimated simultaneously. Both temporary and permanent emigration of the household are addressed. The results of the empirical estimation reveal that families participating in social organizations are more likely to send siblings abroad permanently, as they may receive from the social network important information that is crucial for permanent emigration. Hence, social capital performs a role as complement to permanent emigration. On the other hand, social capital is associated with a lower probability of moving temporarily. This may indicate that families resort to social capital rather than to temporary circular migration to overcome contingent liquidity constraint and therefore social capital is a substitute for temporary emigration.
Keywords: O15; 330; International Migration; Social Capital; Information Network